Staphylococcus aureus triggers a shift from influenza virus–induced apoptosis to necrotic cell death. Issue 5 (11th January 2018) - Van Krüchten, Andre; Wilden, Janine J.; Niemann, Silke; Peters, Georg; Löffler, Bettina; Ludwig, Stephan; Ehrhardt, Christina
Abstract : Superinfections with Staphylococcus aureus are a major complication of influenza disease, causing excessive inflammation and tissue damage. This enhanced cell‐damaging effect is also observed in superinfected tissue cultures, leading to a strong decrease in overall cell viability. In our analysis of the underlying molecular mechanisms, we observed that, despite enhanced cell damage in superinfection, S. aureus did not increase but rather inhibited influenza virus (IV)‐induced apoptosis in cells on the level of procaspase‐8 activation. This apparent contradiction was solved when we observed that S. aureus mediated a switch from apoptosis to necrotic cell death of IV‐infected cells, a mechanism that was dependent on the bacterial accessory gene regulator ( agr ) locus that promotes bacterial survival and spread. This so far unknown action may be a bacterial strategy to enhance dissemination of intracellular S. aureus and may thereby contribute to increased tissue damage and severity of disease.—Van Krüchten, A., Wilden, J. J., Niemann, S., Peters, G., Löffler, B., Ludwig, S., Ehrhardt, C. Staphylococcus aureus triggers a shift from influenza virus‐induced apoptosis to necrotic cell death. FASEB J. 32, 2779–2793 (2018). www.fasebj.org